EFEKTIVITAS METODE BERCERITA DALAM MENINGKATKAN KARAKTER ANAK DI TK MAWAR KECAMATAN SOMBA OPU KABUPATEN GOWA - Nasaruddin R; Sadaruddin (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2019)
Abstract. The Effectiveness of Storytelling Method in Improving the Character of Children in Mawar Kindergarten, Somba Opu District, Gowa Regency. This study aimed to determine the character of early childhood and know the effectiveness of the method of storytelling in improving the character of early childhood in Mawar Kindergarten, Somba Opu District, Gowa Regency. The research hypothesized the storytelling was an effective method in improving the character of children in Mawar Kindergarten, Gowa Regency. The research method was weak experimental with one-shot-case-study design. The research targets were children aged 5-6 years or B.1 group in Mawar Kindergarten, Gowa Regency with 13 children. The data analysis technique used in this research was descriptive statistical analysis technique. Data from observations were analyzed in descriptive quantitative to explain the increase of children character aged 5-6 years. The results of data analysis proved that the method of storytelling was effective in improving the character of children, the value of Sig. (2-tailed) <0.05 so that H0 was rejected and Ha was accepted, which indicated the effectiveness of storytelling method in improving the character of children in Mawar Kindergarten, Somba Opu District, Gowa Regency, Makassar City.